2020
DOI: 10.1016/j.stemcr.2020.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A Single Metabolite which Modulates Lipid Metabolism Alters Hematopoietic Stem/Progenitor Cell Behavior and Promotes Lymphoid Reconstitution

Abstract: Summary Fatty acid β-oxidation (FAO), the breakdown of lipids, is a metabolic pathway used by various stem cells. FAO levels are generally high during quiescence and downregulated with proliferation. The endogenous metabolite malonyl-CoA modulates lipid metabolism as a reversible FAO inhibitor and as a substrate for de novo lipogenesis. Here we assessed whether malonyl-CoA can be exploited to steer the behavior of hematopoietic stem/progenitor cells (HSPCs), quiescent stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In line with this concept, we have recently shown that malonyl-CoA affects HSCs (Giger et al, 2020). Malonyl-CoA is the endogenous inhibitor of CPT1A and at the same time, a key substrate for FASN (Box 1).…”
Section: Modulation Of Lipid Metabolism Influences Hsc Behaviormentioning
confidence: 76%
See 2 more Smart Citations
“…In line with this concept, we have recently shown that malonyl-CoA affects HSCs (Giger et al, 2020). Malonyl-CoA is the endogenous inhibitor of CPT1A and at the same time, a key substrate for FASN (Box 1).…”
Section: Modulation Of Lipid Metabolism Influences Hsc Behaviormentioning
confidence: 76%
“…The addition of this single metabolite to a classical HSC culture medium is sufficient to increase mouse and human HSC numbers in vitro. Furthermore, mouse HSCs grown in this condition have an enhanced lymphoid repopulation capacity upon transplantation in vivo (Giger et al, 2020). With aging, HSCs display a myeloid bias and fewer lymphoid cells are produced, which can lead to reduced immune functions (Kovtonyuk et al, 2016).…”
Section: Modulation Of Lipid Metabolism Influences Hsc Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The breakdown of lipids, termed fatty acid β-oxidation (FAO), is increased in myeloid malignancies associated with enhanced autophagy, which, in turn, also supports OXPHOS specifically in malignant cells but not in normal cells; this leads to proliferation and growth of malignant clones [ 42 ]. Thus, pharmacological modulation of FAO, e.g., with the reversible FAO inhibitor malonyl-CoA, is considered a potential therapeutic intervention to modulate malignant cell fate and, possibly, to influence normal hematopoiesis [ 43 ].…”
Section: Metabolic Changes In the Hspc Poolmentioning
confidence: 99%
“…Cellular metabolism has emerged as a key player in the regulation of immune function [ 7 9 ], starting already at the level of myeloid versus lymphoid lineage decision [ 10 , 11 ] and greatly affecting cellular behaviour in the mature immune cells. Several recent studies have suggested that an altered cellular metabolism in aged macrophages might directly contribute to the pro-inflammatory signature [ 12 14 ].…”
mentioning
confidence: 99%